(3JYdjbI Ydi efgL GdebGds - (3GdHgHgGfj, eMeO GdHgHgGfj, eMeO HGbQ Hf eMeO Cced GdCUagGfj, J (B1205(3g` (B1891(3es
(3ChdgG (B:s
(3ChdgG(B: (3deG GfJHgJ HacQj GdaGJQ Ydi JMbjbGJ aj GdQLGd hYKQJ HJJHYj GdbGUQ Ydi GaGOGJs
(3BNQgG (B:s
(3BNQgG(B: (3GdHRjYjI aQbI aj GdNWGHjI jbhdhf HEeGeI HRjY HYO GHf GdNWGH hCf cd eDef jhMi Edjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B3: 154s
(3GdPQjYI Edi JUGfja GdTjYI, L (B4: 163s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs